Presbiterianismo em mutação : o caso da Chácara Primavera - Filgueiras, Amauri Vassão (2017)
The present content is the result of a multidisciplinary effort, the combination of several lenses through which we intend to analyze some aspects present in the process of mutation of the religious field of the Presbyterian Church of Brazil, IPB. The general objective is to gather, classify, identify and evaluate some of the most significant historical, sociological and religious elements that enable understanding of the dynamics of changes under way within the field of conservative Presbyterianism. It is the reading of an ecclesiastical network that historically operates from a rigid bureaucratic control based on a conciliar pyramidal system, an institution that expresses itself from a spirit of rationalist dogmatism and ethical rigorism, which has resulted in a pronounced difficulty of cultural insertion and low numerical growth in relation to other Brazilian evangelical churches. However, the denomination has shown signs of plurality, openness and reduced levels of control and interference of the councils on local churches and their leadership. The Presbyterian Church Chácara Primavera, based in the city of Campinas, SP, was used as a clipping and object of analysis, which will serve as a sample of a framework that points to a reconfiguration of the relations system within the IPB field. Organized officially in March 2004, the community draws attention for a number of reasons: its exponential numerical growth well above the denomination levels, the incorporation of innovative practices in its liturgical and methodological environments - in comparison to IPB's habits - the dynamics adopted in the appropriation of themes and cultural icons with the purpose of evaluating them from a conservative theological perspective. It should be pointed out, above all, that Chácara Primavera acts as a center for irradiating a movement that has influenced an ever wider sphere of Presbyterian pastors and leaders, and others, regarding the communication of vision, concepts and practices to processes of church planting moving with expressive autonomy within the sphere of IPB. As for the applied methodology, the itinerary of the bibliographic research was chosen from the analysis of books, theses, dissertations, articles and documents generated by the IPB councils made available on the Internet.